ANALISIS BUKU AL BIDAYAH DAN AL MIFTAH LIL ‘ULUM : (Simplifikasi atau Sistematisasi) - Maturedy, Faris; Amirul Mukminin (Fakultas Tarbiyah Universitas Ibrahimy, 2024)
The rules of Arabic grammar are usually hard to understand for a new student. This motivates scholars who study classic educational materials to introduce new ideas that help beginner students quickly grasp the fundamentals of Arabic grammar. These learning innovations include the books Nahwu Sharaf Al Bidayah and Al Miftah lil Ulum. Each of these two books possesses unique traits. The researcher intends to study these features to verify the location of the two books. Researchers utilize qualitative methodologies employing a content analysis framework. The primary data sources for this research are the books Nahsu Sharaf Al Bidayah and Al Miftah lil 'Ulum. The data was analyzed based on the concepts of renewal in learning Arabic grammar after it was obtained. The research findings indicate that the book Nahwu Sharaf Al Bidayah promotes organization and analytical reasoning while engaging with Arabic literature. The book Al Miftah lil 'Ulum focuses on simplifying and presenting content in an engaging manner.